Empowering patient-physician interactions: impact on patient trust - Ouschan, Robyn; Sweeney, Jillian; Johnson, L. (Deakin University, 2005)
Several trends in the healthcare industry are bringing patient empowerment to the forefront, however, at the same time cost cutting and managed health care policies are also eroding patient trust. While patients differ in their desire to actively participate in and take on responsibility for medical-decision making, some health care conditions such as chronic illnesses (e.g., diabetes) require a significant amount of self-management and thus call for a collaborative patient-physician relationship. This study examines whether empowering patient-physician consultations measured through three patient empowerment dimensions (patient control, patient participation, physician support) enhance patients trust in their physician. The results of a comprehensive survey of patients with chronic illness conditions support that all three patient empowerment dimensions have a positive impact on patient trust.